Turkish folk medicinal plants, VIII: Lalapaşa (Edirne) [Türkiye'nin halk ilacı bitkileri, VIII: Lalapaşa (Edirne)] - EMRE, GİZEM (Marmara University, 2010)
In this study, the folk medicinal plants of Lalapaşa (Edirne) were researched. During the field works, the information were obtained from local healers, experienced adults and patients by personal interviews and the specimens of the plants were collected. According to the results of the identifications of the specimens, 55 plant taxa are used in therapy in Lalapaşa. These are presented in a table in the text. Among them 44 taxa are wild and 11 taxa are cultivated plants. The folk medicinal plants are mostly used for stomach ailments, hemorrhoids, diabetes, cold and warts.
Keywords: Edirne; Folk medicine; Lalapaşa; Medicinal plants; Turkey